Positioning and navigation of mobile robot - Mokhtar, N.; Sugisaka, M.; Lung, L.T.; Hamzah, A.; Mubin, M.; Md Shah, N. (Artificial Life and Robotics, 2008)
Positioning tracking is not a new idea as we have been seen from the ability of the GPS (Global Positioning System) to track the position of the object, in general with acceptable accuracy but the cost of GPS installation is expensive. However, in the case of detecting the exact position in signal-blocked closed environment (e.g. inside building, forest, mines and others); the accuracy factor provide by GPS is low. Thus, this project presents a positioning tracking system that is able to track the movement of an object within a small area or inside buildings. A complete set of the positioning tracking system consists of a pair of computer mechanical mouse and a microcontroller. From the position displayed on the computer screen, the position of the object can be located. The pair of mouse detects each movement of the object and sends the movement data to microcontroller. Linear, angular displacement and positioning calculation are also being discussed. From the results, it's shown that the positioning system is applicable. However, some small errors are also occurred but in acceptable range.